2016
DOI: 10.1007/s00294-016-0644-9
|View full text |Cite
|
Sign up to set email alerts
|

Stress sensitivity of a fission yeast strain lacking histidine kinases is rescued by the ectopic expression of Chk1 from Candida albicans

Abstract: The development of new drugs against the pathogenic yeast Candida albicans is compelling and the evolution of relevant bioassays is important to achieve this goal. Promising drug targets are proteins that lack human counterparts which are true for the His-to-Asp phosphorelay signal transduction systems, important for stress sensing in bacteria, fungi, and plants. In the pathogenic yeast, Candida albicans, the CaChk1 histidine kinase is a trigger of the pathway that leads to a switch from yeast to hyphal growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Several studies, including our previous study focusing on class III HHK (Os-1 ortholog) in human dimorphic pathogens, have revealed conserved roles in fungicide resistance, osmotic stress resistance and pathogenicity, in addition to roles in cell wall integrity, asexual development and dimorphism ( 6 , 17 , 33 , 34 ). Furthermore, SlnA (class VI) in T. marneffei , Chk1 (class VIII) in C. albicans , and TcsA (class IV) in Aspergillus nidulans were revealed to be associated with osmotic stress resistance, HOG MAPK regulation, the dimorphic transition and development under standard growth conditions ( 7 , 35 ). As multiple histamine kinases may compensate for each other in S. schenckii ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including our previous study focusing on class III HHK (Os-1 ortholog) in human dimorphic pathogens, have revealed conserved roles in fungicide resistance, osmotic stress resistance and pathogenicity, in addition to roles in cell wall integrity, asexual development and dimorphism ( 6 , 17 , 33 , 34 ). Furthermore, SlnA (class VI) in T. marneffei , Chk1 (class VIII) in C. albicans , and TcsA (class IV) in Aspergillus nidulans were revealed to be associated with osmotic stress resistance, HOG MAPK regulation, the dimorphic transition and development under standard growth conditions ( 7 , 35 ). As multiple histamine kinases may compensate for each other in S. schenckii ( Fig.…”
Section: Discussionmentioning
confidence: 99%